PENGARUH PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS VIII SMP NEGERI 1 PAYAKUMBUH - Rahma, Silvia Hanifah (Departemen Matematika, 2024)
Abstract – Numeracy literacy is a required skill in the independent curriculum. Numeracy literacy is a skill that must be possessed by students in using various kinds of numbers and symbols related to mathematics to solve contextual problems. But in practice, this ability is still relatively low in class VIII SMP Negeri 1 Payakumbuh. This can be improved by applying the Realistic Mathematics Education (RME) approach. This study aims to determine whether the numeracy literacy skills of students who learn with the Realistic Mathematics Education (RME) approach are better than the numeracy literacy skills of students who learn with conventional approaches. This research is categorized as a quasy experiment with a nonequivalent post-test only control group design. The research instrument used was a numeracy literacy test which was analyzed using the t-test. Based on the analysis of the test results, the average score of the experimental class was 18.31 and the control class was 15.56. The numeracy literacy test results after analyzing the data obtained that at a significant level of 0.05 by conducting a t-test obtained P-value = 0.001, because the P-value < a then H0 is rejected. This shows that the numeracy literacy skills of students who use the Realistic Mathematics Education (RME) approach are better than students who use conventional approaches in class VIII SMP Negeri 1 Payakumbuh.Keywords– Realistic Mathematics Education (RME) Approach, Numeracy Literacy Skills, Conventional Approach